PEMETAAN DAN PREDIKSI PERUBAHAN GARIS PANTAI DI KECAMATAN UJUNGPANGKAH, KABUPATEN GRESIK, JAWA TIMUR, DI BADAN INFORMASI GEOSPASIAL, BOGOR, JAWA BARAT - Sanydo P.Cesar (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2017)
This study aims to determine the shoreline changes that occurred in Ujungpangkah District, Gresik Regency, East Java. The objective of this internship practice is to know the shoreline changes with time series satellite image data from 1999 to 2015 and UAV data of 2016, also able to analyze the cause and effect of coastline changes that occurred in Karangrejo-Gresik Sub-district.The method used in this research is using Arc.Gis overlay method. The input results are then predicted by using the exponential linear regression equation.The results showed the resistance of the 2nd zone's cumulative change of -2657 meters from the zero, while the smallest change in point 2 with the change in 2030 was -2211.9 meters from the zero point. Changes of coastline in zone 2 from 2016-2030 will experience habit (abrasion) as much as 1275,5 meter. Predicted zone 3 shoreline in the year 1999-2030from 2237.8 meters, while the most change occurred at point 8 with change in the year 2030as much as 589,4 meter from zero. The result of coastline a change in zone 1 from 2016-2030 will increase (accretion) as much as 480 meters.